Behavioural and Physiological Responses of Gammarus pulex Exposed to Cadmium and Arsenate at Three Temperatures: Individual and Combined Effects - Vellinger, Céline; Felten, Vincent; Sornom, Pascal; Rousselle, Philippe; Beisel, Jean-Nicolas; Usseglio-Polatera, Philippe (PLOS ONE, 2012)
This study aimed at investigating both the individual and combined effects of cadmium (Cd) and arsenate (AsV) on the physiology and behaviour of the Crustacean Gammarus pulex at three temperatures (5, 10 and15°C). G. pulex was exposed during 96 h to (i) two [Cd] alone, (ii) two [AsV] alone, and (iii) four combinations of [Cd] and [AsV] to obtain a complete factorial plane. After exposure, survival, [AsV] or [Cd] in body tissues, behavioural (ventilatory and locomotor activities) and physiological responses (iono-regulation of [Na+] and [Cl−] in haemolymph) were examined. The interactive effects (antagonistic, additive or synergistic) of binary mixtures were evaluated for each tested temperature using a predictive model for the theoretically expected interactive effect of chemicals. In single metal exposure, both the internal metal concentration in body tissues and the mortality rate increased along metallic gradient concentration. Cd alone significantly impaired both [Na+] and [Cl−] while AsV alone had a weak impact only on [Cl−]. The behavioural responses of G. pulex declined with increasing metal concentration suggesting a reallocation of energy from behavioural responses to maintenance functions. The interaction between AsV and Cd was considered as ‘additive’ for all the tested binary mixtures and temperatures (except for the lowest combination at 10°C considered as “antagonistic”). In binary mixtures, the decrease in both ventilatory and locomotor activities and the decline in haemolymphatic [Cl−] were amplified when respectively compared to those observed with the same concentrations of AsV or Cd alone. However, the presence of AsV decreased the haemolymphatic [Na+] loss when G. pulex was exposed to the lowest Cd concentration. Finally, the observed physiological and behavioural effects (except ventilation) in G. pulex exposed to AsV and/or Cd were exacerbated under the highest temperature. The discussion encompasses both the toxicity mechanisms of these metals and their interaction with rising temperature.